The impact of stock market performance on economic growth in Malawi - Ng’oma, Diana Kisyombe (Research of GSB, 2019)
This study investigated the causal relationship between the performance of the Malawi Stock Exchange (MSE) and economic growth in Malawi using quarterly data for the period 2003 to 2017. Stock market performance was measured using four indicators: the all share price index, total stock market capitalisation, stock market liquidity, and the number of shares traded. Economic growth was measured by real Gross Domestic Product (GDP). The Autoregressive Distributed Lag (ARDL) model was used to test for the existence of a long- run co-integrating relationship between the variables, while Granger causality tests, impulse response functions and variance decomposition analyses were employed to examine the short- run dynamics. The co-integration tests found no evidence of a long-run relationship between real GDP and all measures of stock market performance. However, there was evidence of the existence of shortrun relationships, with a positive and significant contemporaneous relationship noted between real GDP and stock market capitalisation and a negative and significant relationship between real GDP and market liquidity. The Granger causality tests revealed the following intertemporal relationships: bidirectional causality between real GDP and stock market liquidity and unidirectional causality from stock market capitalisation to real GDP and changes in the all share price index to real GDP. The impulse response functions and variance decompositions further revealed real GDP reacts highly to a shock in market capitalisation than to other variables and a shock in real GDP causes a higher fluctuation in liquidity than in any other variables. The findings of this study thus show that there is short-term causality between the performance of the MSE and economic growth in Malawi albeit that no long-run relationship exists. In light of these results, specific policy recommendations are provided for various stakeholders so as to enhance economic growth in Malawi. Suggestions for future research are also given.